An evaluation of inflammation with mean platelet volume in children with celiac disease (Annals of Medical Research, 2021)
Aim: The purpose of this study was to evaluate mean platelet volume and platelet distribution width in children with celiac disease.Material and Methods: Fifty children with celiac disease (18 boys, 32 girls) and 63 healthy volunteer children (23 boys, 40 girls) were included in the study. Demographic features such as age, and gender and laboratory values such as platelet count, mean platelet volume, and platelet distribution width were recorded from the patients’ files.Results: Fifty children with celiac disease (18 boys, 32 girls) and 63 healthy volunteer children (23 boys, 40 girls) were included in the study. No statistically significant differences were determined between the celiac disease group and the healthy control group in terms of platelet counts (275,418±70,657/mm3 and 280,888±61,290/mm3, respectively, p=0.661), platelet distribution width (19.27±1.14 fL and 19.16±1.13 fL, respectively, p=0.670) or mean platelet volume (7.31±1.36 fL and 7.38±1.45 fL, respectively, p=0.779). At ROC analysis, a cut off value was determined for platelet distribution width of 18.2 fL with 24.00% sensitivity and 87.30% specificity (AUC: 0.504, 95% Cl: 0.408-0.599 and p=0.947). A cutoff value for mean platelet volume of 0.74 was calculated with 72.00% sensitivity and 44.44% specificity (AUC: 0.520, 95% Cl: 0.424-0.615 and p=0.708).Conclusions: Mean platelet volume values in children with celiac disease were no different to those of the healthy control group. We think that the absence of any change in mean platelet volume, values in children diagnosed with celiac disease may be related to a short duration of inflammation.
Keywords: Child; celiac disease; inflammation; mean platelet volume